Semantic Research in the Book “Mir’āt al-Mafātīḥ” by Mubarakpuri (d. 1414 AH), Part One - Hamed, Dr.Hadi Shehab (Thi Qar Arts Journal, 2024)
The aim of this study is to highlight the semantic and non-semantic issues in understanding the noble prophetic texts. It addresses semantic issues such as homonymy, synonymy, and antonymy, as well as non-semantic concepts like generalization, expansion, and clarification of meaning and their impact on the texts of the Hadith. Semantics is considered one of the most important and honorable sciences after the Quran and the Sunnah, as the Sunnah clarifies the rulings of Islamic law and elucidates the general and detailed meanings of Quranic verses. This is especially significant given that its source is divine revelation.